Increased susceptibility to SARS‐CoV‐2 infection in patients with reduced left ventricular ejection fraction. (18th November 2020) - Matsushita, Kensuke; Marchandot, Benjamin; Carmona, Adrien; Curtiaud, Anais; El Idrissi, Anis; Trimaille, Antonin; Kibler, Marion; Cardi, Thomas; Heger, Joe; Hess, Sebastien; Reydel, Antje; Jesel, Laurence; et al.
Abstract: Aims: Cardiovascular disease has been recognized as a major determinant of coronavirus disease 2019 (COVID‐19) vulnerability and severity. Angiotensin‐converting enzyme (ACE) 2 is a functional receptor for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and is up‐regulated in patients with heart failure. We sought to examine the potential association between reduced left ventricular ejection fraction (LVEF) and the susceptibility to SARS‐CoV‐2 infection. Methods and results: Of the 1162 patients with acute coronary syndrome (ACS) who underwent percutaneous coronary intervention between February 2014 and October 2018, we enrolled 889 patients with available clinical follow‐up data. Follow‐up was conducted by telephone interviews 1 month after the start of the French lockdown which began on 17 March 2020. Patients were divided into two groups according to LVEF <40% (reduced LVEF) ( n  = 91) or ≥40% (moderately reduced + preserved LVEF) ( n  = 798). The incidence of COVID‐19‐related hospitalization or death was significantly higher in the reduced LVEF group as compared with the moderately reduced + preserved LVEF group (9% vs. 1%, P  < 0.001). No association was found between discontinuation of ACE‐inhibitor or angiotensin‐receptor blockers and COVID‐19 test positivity. By multivariate logistic regression analysis, reduced LVEF was an independent predictor of COVID‐19 hospitalization or death (odds ratio: 6.91, 95% confidence interval: 2.60 to 18.35, P  < 0.001). Conclusions: In a large cohort of patients with previous ACS, reduced LVEF was associated with increased susceptibility to COVID‐19. Aggressive COVID‐19 testing and therapeutic strategies may be considered for patient with impaired heart function.